Influência do solo e do tamanho de semente no crescimento e sobrevivência de nove espécies arbóreas tropicais em área ripária degradada - Scaloppi, Julie Christine (Universidade Federal de São Carlos, 2017)
Understanding the mechanisms that involves the relations between plants and the abiotic environment is vital for the knowledge of the successional dynamics of native vegetation in degraded areas. Several studies have shown that seed size positively influences survival and negatively influences the growth of plants in the early stages of their development. However, soil conditions can influence these relationships, since the availability of soil resources can generate variations in plant survival and growth. This study evaluated the influence of seed mass and soil properties on the performance of nine native tree species that formed a seed size gradient: Cedrela fissilis, Pterogyne nitens, Cariniana estrellensis, Enterolobium contortisiliquum, Copaifera langsdorffii, Enterolobium timbouva, Platypodium Elegans, Schizolobium parahyba and Hymenaea courbaril. These species were introduced as seedlings with the objective of restoring a degraded riparian area. From a conceptual model, we simultaneously evaluated the survival and growth of plants in function of seed mass, initial plant size and soil chemical properties at four time intervals over the first three years after planting. During this period, the seed mass and the chemical properties of the soil influenced directly and indirectly, through initial plant size, growth and survival. In the first time interval, the period between planting and the two subsequent months, seed mass was the main factor influencing survival and growth rate, but the initial diameter (plant diameter when they where planted) and soil fertility also influenced growth. In the second time interval (between the first two months and the end of the first year), seed mass and initial diameter positively influenced survival. In this period, the initial diameter, soil fertility and seed mass influenced the growth rate. In the following two years, the survival of young plants was influenced only by their initial diameter and plant growth was influenced by seed mass and influenced negatively by soil potential acidity. In general, the smaller seed species generated smaller individuals and had a faster growth until the end of the first year, whereas the larger seed species generated larger individuals, but with a slower and constant growth, surpassing the growth of the small seeded species during the second year. Larger seeds also achieved higher survival rates during the first year. Larger plants grew more by the end of the first year and had greater chances of survival after the first year. Soil fertility stimulated plant growth resulting in larger plants, while potential acidity variation negatively influenced performance in some study periods. Our results corroborate with the hypothesis of seedling size and the metabolic hypothesis. Prior analysis of soil properties, improvement of edaphic conditions in degraded areas and consideration of functional traits in the choice of tropical tree species can improve the effectiveness of restoration projects.
Keywords: Desenvolvimento inicial de plantas; Fertilidade do solo; Modelo estrutural; Performance de espécies arbóreas; Restauração de florestas ripárias; Initial plant development; Restoration of riparian forests; Soil fertility; Structural model; Tree species performance; CIENCIAS BIOLOGICAS